2019
DOI: 10.1155/2019/5451038
|View full text |Cite
|
Sign up to set email alerts
|

The Lysine Demethylase KDM5B Regulates Islet Function and Glucose Homeostasis

Abstract: Aims. Posttranslational modifications of histones and transcription factors regulate gene expression and are implicated in beta-cell failure and diabetes. We have recently shown that preserving H3K27 and H3K4 methylation using the lysine demethylase inhibitor GSK-J4 reduces cytokine-induced destruction of beta-cells and improves beta-cell function. Here, we investigate the therapeutic potential of GSK-J4 to prevent diabetes development and examine the importance of H3K4 methylation for islet function. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Recently, KDM3A, a demethylase that removes methyl form histone lysine H3K9, has been reported to promote urinary bladder cancer progression by enhancing glycolysis through coactivation of hypoxia inducible factor 1α [34]. KDM5B, another demethylase, has been reported to participate in the regulation of islet function and glucose homeostasis [35]. We also notice that the loss of KDM4B has been reported to result in metabolic dysfunction [17].…”
Section: Discussionmentioning
confidence: 63%
“…Recently, KDM3A, a demethylase that removes methyl form histone lysine H3K9, has been reported to promote urinary bladder cancer progression by enhancing glycolysis through coactivation of hypoxia inducible factor 1α [34]. KDM5B, another demethylase, has been reported to participate in the regulation of islet function and glucose homeostasis [35]. We also notice that the loss of KDM4B has been reported to result in metabolic dysfunction [17].…”
Section: Discussionmentioning
confidence: 63%
“…H3K4me1/2/3, H3K36me2/3, and H3K79me2 are correlated with transcriptional activation ( Zheng et al, 2021 ). A genome-wide study of these modifications revealed that these modifications played critical roles in the specific promoters and enhancers of the islet and pathogenesis of diabetes ( Backe et al, 2019 ).…”
Section: Histone Methylation In Type 2 Diabetesmentioning
confidence: 99%
“…For example, individuals with type 2 diabetes had higher DNMT3B levels in cultured myotubes [5] and decreased TET1 expression in adipose tissue [6] vs tissue from individuals without type 2 diabetes, while palmitate exposure decreased DNMT3A and DNMT1 expression in human pancreatic islets [11]. Several studies have further shown that inhibitors of HDACs and histone demethylases, or silencing and overexpressing those enzymes, impact beta cell function and insulin secretion [9,[46][47][48][49]. For example, DNA methylation is decreased, and expression of HDAC7 increased in pancreatic islets from donors with type 2 diabetes [49].…”
Section: Dnmt Dna Methyltransferase Hdac Histone Deacetylasementioning
confidence: 99%